PROSFEK PENGEMBANGAN BAKTERI ENDOFIT SEBAGAI AGENS HAYATI PENGENDALIAN NEMATODA / The Prospect of Developing Endophytic Bacteria as Nematodes Biological Control - Rita Harni (Puslitbang Perkebunan, 2016)
Plant parasitic nematodes are one of the most important plant pests that attack a variety of estate crops like pepper, patchouli, coffee, tobacco and ginger. Meloidogyne, Pratylenchus, and Radopholus the most destructive parasitic nematodes in these commodities. Yield Losses due to nematodes on black pepper can reduce the production of 32%, 75% in patchouli, 58% ginger and 57% at the coffee. Controlling nematodes are widely used at this time are endophytic bacteria. Endophytic bacteria are live bacteria that colonize the host plant tissues without causing any negative effects, but giving many benefits to their host, because it can be as biological agents, and trigger the growth of plants. Mechanism of action endophytic bacteria in controlling nematodes are induce resistance, competition nische, and produce anti-nematode metabolites, that affect on the penetration, reproduction and nematode populations. The use of endophytic bacteria Achromobacter xylosoxidans (TT2), Bacillus cereus (MSK), Alcaligenes faecalis (NJ16), Bacillus subtilis (NJ57) and Pseudomonas putida (EH11) on patchouli can suppress nematode populations of P. brachyurus at 54.8 to 70.6 %. Endophytic bacteria Bacillus sp. and Pseudomonas sp. can reduce the incidence of yellow disease and nematode populations of R. similis and M. incognita, as well as increase the number of flowers/ node and the wet weight of the black pepper, and endophytic bacteria Bacillus pumilus and B. mycoides can suppress the population and the number of root knot nematode M. incognita 33 - 39% of the coffee plant. Development of endophytic bacteria to control parasitic nematodes in estate crop is very promising because of endophytic bacteria as a biological control agent is superior to another agent, can be isolated from all parts of the plant, propagation media inexpensive, easy application and not repetitive. Endophytic bacteria may be of biological agents and plant growth promoters, its use can reduce synthetic pesticides and synthetic fertilizers so very supportive to sustainable agriculture.